Current career situations of Chinese pharmacovigilance professionals working for pharmaceutical companies: an exploratory survey - Yalan Tang; Yan Liu; Hongli Liao; Yonghua Yuan; Qihua Jiang (BMC, 2023)
Abstract Background Pharmacovigilance in China has experienced rapid development in the past 30 years. The implementation of Good Pharmacovigilance Practice in China since the end of 2021 heralds a new era of pharmacovigilance affairs, which puts forward higher requirements for the quantity and quality of pharmacovigilance personnel. This study aimed to preliminarily explore the current career situations of pharmacovigilance professionals working in China for pharmaceutical companies. Methods A questionnaire was adapted from research in the USA and Europe with the help of several pharmacovigilance experts. Snowball sampling was used to conduct an exploratory survey to obtain the frequency of basic demographic information, work status, and career expectations of pharmacovigilance professionals working for pharmaceutical companies. Results The personnel engaged in pharmacovigilance work for pharmaceutical companies were mainly medical or pharmaceutical undergraduates within 3 years of graduation. Their work intensity and pressure were relatively high. The training provided by their universities and enterprises could not well meet their needs to improve their job competence. Although they were optimistic about pharmacovigilance and will not change their career, most of them were planning to change their employers. Conclusion There was a gap between the demand and supply of pharmacovigilance personnel. Relevant regulatory authorities and industry associations should guide higher education institutions to collaborate with pharmacovigilance specialists to strengthen pharmacovigilance education for medical or pharmaceutical students, on the basis of which pharmacovigilance certification courses and continuing education courses can be developed. Meanwhile, pharmaceutical enterprises should consider reasonably adjusting work intensity and income to avoid a high turnover rate.